On the Question of Neoclassical Compounds in Lithuanian - Inčiuraitė, Lina (Verbum, 2013)
In Lithuanian, word formation processes have been given detailed consideration with regard to their morphological properties. However, neoclassical compounds have received exiguous attention. They are described as formations consisting of Greek and Latin bound stems. This article aims at examining the structure of neoclassical compounds in Lithuanian. It is neither simple nor straightforward to determine the morphological status of the constituent items of neoclassical compounds and to differentiate them from prefixes, initial combining forms, final combining forms, constituents or affixoids. Due to their heterogeneous nature, linguists treat them differently as no strict criteria have been applied for their delimitation. When words with neoclassical elements appear in the Lithuanian language, they usually adapt to this language’s phonological and morphological system. The analysis of neoclassical compounds in Lithuanian shows that not all neoclassical elements have the same positional constraints. Some of them can appear both in initial or final position, some only in initial position, while others only in final position. Furthermore, neoclassical compounds in Lithuanian consist of two or more bound stems which give rise to new neoclassical compounds. As far as the combinability properties of neoclassical elements are concerned, they appear in combinations with one another, with words of English origin as well as with Lithuanian native forms. Neoclassical formations can also contain international or Lithuanian suffixes. Such formations constitute endocentric structures in particular.